Optimizing Public Health through Nutritional Status Assessment and Nutrition Education during Car Free Day in Padang City - Elda, Frima; Novirsa, Randy; Kasra, Kamal; Markolinda, Yessy; Amalia, Revi; Azmi, Fadilla; Fatrima Surya, Rezi; Delviana, Adelia (Warta Pengabdian Andalas, 2025)
Public health is one of the key aspects of sustainable development. This community service activity aims to improve public health through nutritional status assessments conducted during the Car Free Day (CFD) event in Padang City. The methods used include nutritional status measurement, nutrition education, and the promotion of healthy lifestyles. Health measurements included assessments of body weight, height, fat mass, muscle mass, blood pressure, blood sugar levels, uric acid levels, and hemoglobin levels. Education was delivered through interactive sessions and the distribution of leaflets on healthy eating patterns and clean-living behaviors. The impact of the education was evaluated qualitatively through testimonials from participants who took part in both the health check and educational sessions. Participants shared their experiences regarding changes in their dietary habits and healthy lifestyle practices after participating in the program. Several participants stated that they had begun adopting healthier lifestyles, such as paying more attention to food intake, increasing physical activity, and feeling the benefits of a fitter body. Based on these testimonials, this activity demonstrated an increase in awareness and the adoption of healthy living behaviors among the community. Therefore, interventions through health assessments and nutrition education have been proven to contribute to encouraging positive behavioral changes within the community.